Application of Liquid Organic Fertilizer Human Urine Fermentation to Increase Growth of Corn Plants in Inceptisols Kwala Bekala - Sefriansyah Putra; Mukhlis Mukhlis; Mohammad Madjid B Damanik (Universitas Sumatera Utara, 2018)
Green house study to increase growth of corn plants with application human urine fermentation as liquid organic fertilizer in Inceptisols Kwala Bekala. Research using randomized block non factorial design with 5 levels of dosage treatmenthuman urine fermentation that is: 0 mL/pot (P0), 25 mL/pot (P1), 50 mL/pot (P2), 75 mL/pot (P3) and100 mL/pot (P4) with 5 replications. Parameter that measured are soil pH, organic C, N-total, P-available, K-exchangeable, plant height, root dry weight, shoot dry weight, N, P and K uptake in Laboratory. Result of this research showed that application human urine fermentation can improve soil pH, organic C, N-total, P-available, K-exchangaeble, plant Height, root and shoot dry weight, and uptake N, P, K growth of corn plants. Best human urine fermentation dose on this research is 75 mL/pot (P3). Keywords: Human urine fermentation, Inceptisols Kwala Bekala, Nutrient, Organic fertilizer.